The cement-bentonite diaphragm of the Malagrotta municipal waste landfill (Rome, Italy): efficiency analysis - Braga, Franco; Prestininzi, Alberto (Italian journal of engineering geology and environment, 2021)
<span data-sheets-value="{"1":2,"2":"The MSW landfill of the city of Rome, one of the largest in Europe, was created in the area of Malagrotta. Between the 1950s and the early 1960s, this area hosted important sand and gravel quarries, which supplied aggregates for construction projects, such as those necessary for the rapid urban expansion of Rome after the second world war. The area has a complex stratigraphy, schematically consisting (from top to bottom) of volcanic deposits, sands, gravels, and very compact gray-blue clays. This geological setting, with cavities from the previous quarrying of large volumes of aggregates (estimated at over 200 × 106 m3 in 1987), offered an ideal site for MSW disposal. Remediation and safe confinement projects were undertaken at the landfill site after the issuing of Decree of the President of the Republic 915/82 of 10 September 1982, transposing three European Directives, including Council Directive 75/442/EEC of 15 July 1975 on waste, into the Italian legislation. From a financial and technical-scientific viewpoint, the most important project to make the landfill compliant with the new legislation was the construction of a hydraulic sealing wall around the internal subareas of the landfill that would accommodate MSW. The wall consisted in a plastic diaphragm of variable depth (Fig. 1). This is one of the major barrier walls built in the world for the confinement of MSW landfills (Table 1). As part of the activities undertaken at the Malagrotta landfill site, we investigated the functional efficiency of the diaphragm. Several in situ tests were thus planned and implemented. This paper analyses the results of hydraulic stress tests carried out in appropriate sections, provided with piezometers and other measuring instruments making part of the system for monitoring the entire surface area of the landfill (161 ha). Figure 3 is a sketch of the section used for hydraulic tests, representing the entire confinement system (Fig. 2). The entire set of data confirms the efficiency of the confinement system examined. The results obtained, by imposing Darcy’s solution based on a reductio ad absurdum argument, demonstrates that the cement-bentonite diaphragm is totally “impermeable” and thus fully suitable for performing the function for which it was designed and built (Prestininzi & Romagnoli, 1991). The data shown in Table 2 corroborates this assumption, i.e. the hydraulic heads in V7 and in Z7 are linked by a linear proportionality ratio, connected with a transfer of energy pressure). The findings from our hydrogeological analysis and the application of Darcy’s law were validated by a mechanical analysis of the elastic behaviour of the diaphragm, made up of a cement-bentonite mixture. The results of the application of the equations of the elastic line revealed that the undrained behaviour of the soil-diaphragm system was in line with our analyses based on experimental data from hydraulic tests and statistical tests. By using Equations (3) and (4), we computed the values umax and Aumax for all the time steps ti. Statistical processing of the data enabled us to compare all the available results: piezometric heads in V7, piezometric heads induced in Z7, arrow umax (x = 0), and surface area Aumax acting on the diaphragm. In particular, the comparison highlighted their mutual relationships under the various conditions of stress q, thereby validating the linear proportionality of the diaphragm displacement and the origin of the piezometric changes ΔHZ7. Indeed, the data of Tables 2 and 3 shows the linear proportionality of ratios (V7/Z7) and of changes in hydraulichead with the data connected with the diaphragm displacement, ΔH(Z7)/[(Au)/(umax (x = 0)].The analysis of these results confirmed what we hadobserved during hydraulic investigations: the behaviour of the system, subjected to hydraulic stress tests, proved to be typical of undrained systems, which respond to stress changes with exchanges of energy and induced deformations at constant volume (Figs. 3, 5, 6 a) and b)). After more than 34 years since its construction, the cement-bentonite plastic diaphragm retains an excellent hydromechanical efficiency, allowing it to perform its hydraulic sealing and mechanical elastic behaviour function in the future."}" data-sheets-userformat="{"2":15297,"3":{"1":0},"9":0,"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">The MSW landfill of the city of Rome, one of the largest in Europe, was created in the area of Malagrotta. Between the 1950s and the early 1960s, this area hosted important sand and gravel quarries, which supplied aggregates for construction projects, such as those necessary for the rapid urban expansion of Rome after the second world war. The area has a complex stratigraphy, schematically consisting (from top to bottom) of volcanic deposits, sands, gravels, and very compact gray-blue clays. This geological setting, with cavities from the previous quarrying of large volumes of aggregates (estimated at over 200 × 106 m3 in 1987), offered an ideal site for MSW disposal. Remediation and safe confinement projects were undertaken at the landfill site after the issuing of Decree of the President of the Republic 915/82 of 10 September 1982, transposing three European Directives, including Council Directive 75/442/EEC of 15 July 1975 on waste, into the Italian legislation. From a financial and technical-scientific viewpoint, the most important project to make the landfill compliant with the new legislation was the construction of a hydraulic sealing wall around the internal subareas of the landfill that would accommodate MSW. The wall consisted in a plastic diaphragm of variable depth (Fig. 1). This is one of the major barrier walls built in the world for the confinement of MSW landfills (Table 1). As part of the activities undertaken at the Malagrotta landfill site, we investigated the functional efficiency of the diaphragm. Several in situ tests were thus planned and implemented. This paper analyses the results of hydraulic stress tests carried out in appropriate sections, provided with piezometers and other measuring instruments making part of the system for monitoring the entire surface area of the landfill (161 ha). Figure 3 is a sketch of the section used for hydraulic tests, representing the entire confinement system (Fig. 2). The entire set of data confirms the efficiency of the confinement system examined. The results obtained, by imposing Darcy’s solution based on a reductio ad absurdum argument, demonstrates that the cement-bentonite diaphragm is totally “impermeable” and thus fully suitable for performing the function for which it was designed and built (Prestininzi & Romagnoli, 1991). The data shown in Table 2 corroborates this assumption, i.e. the hydraulic heads in V7 and in Z7 are linked by a linear proportionality ratio, connected with a transfer of energy pressure). The findings from our hydrogeological analysis and the application of Darcy’s law were validated by a mechanical analysis of the elastic behaviour of the diaphragm, made up of a cement-bentonite mixture. The results of the application of the equations of the elastic line revealed that the undrained behaviour of the soil-diaphragm system was in line with our analyses based on experimental data from hydraulic tests and statistical tests. By using Equations (3) and (4), we computed the values umax and Aumax for all the time steps ti. Statistical processing of the data enabled us to compare all the available results: piezometric heads in V7, piezometric heads induced in Z7, arrow umax (x = 0), and surface area Aumax acting on the diaphragm. In particular, the comparison highlighted their mutual relationships under the various conditions of stress q, thereby validating the linear proportionality of the diaphragm displacement and the origin of the piezometric changes ΔHZ7. Indeed, the data of Tables 2 and 3 shows the linear proportionality of ratios (V7/Z7) and of changes in hydraulichead with the data connected with the diaphragm displacement, ΔH(Z7)/[(Au)/(umax (x = 0)].The analysis of these results confirmed what we hadobserved during hydraulic investigations: the behaviour of the system, subjected to hydraulic stress tests, proved to be typical of undrained systems, which respond to stress changes with exchanges of energy and induced deformations at constant volume (Figs. 3, 5, 6 a) and b)). After more than 34 years since its construction, the cement-bentonite plastic diaphragm retains an excellent hydromechanical efficiency, allowing it to perform its hydraulic sealing and mechanical elastic behaviour function in the future.